2022
DOI: 10.3389/fphar.2022.818166
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Pro-Inflammatory Pathways by Ginger and Turmeric Extracts in RAW 264.7 Cells

Abstract: Synergy plays a prominent role in herbal medicines to increase potency and widen the therapeutic windows. The mechanism of synergy in herbal medicines is often associated with multi-targeted behavior and complex signaling pathways which are challenging to elucidate. This study aims to investigate the synergistic mechanism of a combination (GT) of ginger (G) and turmeric (T) extracts by exploring the modulatory activity in lipopolysaccharides (LPS)-induced inflammatory pathways and key molecular targets. A Biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In our previous study, the G and T combination in the specific ratio of 5:2 (w/w) was demonstrated to exhibit synergistic activity in LPS-induced proinflammatory pathways [43].…”
Section: Discussionmentioning
confidence: 96%
“…In our previous study, the G and T combination in the specific ratio of 5:2 (w/w) was demonstrated to exhibit synergistic activity in LPS-induced proinflammatory pathways [43].…”
Section: Discussionmentioning
confidence: 96%
“…NF-kB translocation was determined as described in previous studies [ 23 ]. RAW 264.7 cells were plated in an 8-well Nunc™ Lab-Tek™ II Chamber Slide™ System (Thermo Fisher Scientific, Sydney, Australia) at 20,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…These results showed that the natural-origin compounds contained in ginger exhibit similar pharmacological efficacy to non-steroidal anti-inflammatory drugs ( Kumar et al, 2013 ; Aziz et al, 2015 ; Deng M. et al, 2022 ). It has also been explained that phosphatidylinositol-3-kinase (PI3K), Akt, and NF-κB light chain enhancer of activated B cells are prominent in the mechanism of the anti-inflammatory effect ( Mao et al, 2019 ; Zahoor et al, 2020 ; Zhang et al, 2021 ; Zhou et al, 2022 ).…”
Section: Interaction Of Gingerols With the Immune Systemmentioning
confidence: 99%
“…). It has also been explained that phosphatidylinositol-3kinase (PI3K), Akt, and NF-κB light chain enhancer of activated B cells are prominent in the mechanism of the anti-inflammatory effect (Mao et al, 2019;Zahoor et al, 2020;Zhang et al, 2021;Zhou et al, 2022).…”
mentioning
confidence: 99%